The founder of Cairo : the Fatimid Imam-Caliph al-Mu'izz and his era : an English translation of the text on al-Mu'izz from Idrīs 'Imād al-Dīn's 'Uyūn al-akhbār /: the Fatimid Imam-Caliph al-Mu'izz and his era : an English translation of the text on al-Mu'izz from Idrīs 'Imād al-Dīn's 'Uyūn al-akhbār. (2013) - Qurashī, Idrīs ʿImād al-Dīn, -1467
No abstract available